2001
DOI: 10.1046/j.1365-3024.2001.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrus ovis (Diptera: Oestridae): effects of larval excretory/secretory products on nitric oxide production by murine RAW 264·7 macrophages

Abstract: Larvae of Oestrus ovis (Insecta: Diptera: Oestridae) are common parasites of nasal and sinus cavities of sheep and goats. Previous studies revealed that crude extracts of larvae modify NO synthesis by ovine monocyte derived macrophages. The aim of this study was to investigate the larval excretory/secretory products effects on nitric oxide production by murine tumour macrophages RAW 264.7. Stimulation of RAW macrophages by excretory/secretory products of the three instars larvae (25 microg/ml) significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…As expected, over the period 1994-2000, no seropositive roe deer was detected by ELISA, since the first report dates 2001 [26]. However, 38% (CI [35][36][37][38][39][40][41][42] of roe deer hunted between 2007 and 2014 showed C. stimulator antibodies. It is worth noting that the presence of specific antibodies indicates exposure to the parasite but not necessarily an active infestation.…”
Section: Prevalence and Infestation Intensitysupporting
confidence: 53%
“…As expected, over the period 1994-2000, no seropositive roe deer was detected by ELISA, since the first report dates 2001 [26]. However, 38% (CI [35][36][37][38][39][40][41][42] of roe deer hunted between 2007 and 2014 showed C. stimulator antibodies. It is worth noting that the presence of specific antibodies indicates exposure to the parasite but not necessarily an active infestation.…”
Section: Prevalence and Infestation Intensitysupporting
confidence: 53%
“…By contrast, in vitro assays have demonstrated that O. ovis larval extracts, mainly L2 somatic extracts, induce nitric oxide (NO) production by macrophages . Interestingly, products excreted/secreted by larvae were also able to induce NO production in murine RAW 264.7 macrophages (Tabouret et al, 2001b). Induction of NO in these tumoral cells was principally linked to a 29-kDa protein secreted by the larval salivary glands.…”
Section: Immunostimulationmentioning
confidence: 97%
“…Nitric oxide induces tissue damage, vasodilatation and plasma protein leakage. Thus, although an NO burst may be harmful to the host, the plasma protein leakage and hypersecretion induced by excreted/secreted larval products may be a source of food and nutrients for larvae (Tabouret et al, 2001b(Tabouret et al, , 2003b. -Charrier & Dorchies (1993) reported for the first time that in vitro lymphocyte proliferation decreased and mitotic activity was depleted to levels comparable with those in non-infected lambs on days 19 and 33 post-infection, respectively.…”
Section: Immunostimulationmentioning
confidence: 99%
“…Although their hooks and spines injure the nasal membranes, larval nutrition is not only mechanical but mainly related to a biochemical process and huge nitrogen oxide liberation has been observed. Indeed, Tabouret et al (2001c) have shown, in vitro, that ESP could stimulate nitric oxide production inducing plasma protein leakage. This up regulation is time and dose-dependent.…”
Section: Larval Nutritionmentioning
confidence: 99%